2020
DOI: 10.1101/2020.06.02.20119958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of high-intensity interval training in patients with coronary artery disease after percutaneous coronary intervention: a systematic review and meta-analysis

Abstract: Background: High-intensity interval training, for its characteristic of short-time high oxygen-consumption exercise interphase with periods of low-intensity training or rest for recovery, is easier to persist and execute in cardiac rehabilitation. However, it is little known whether HIIT program has an advantageous effect on patients after percutaneous coronary intervention or not. Methods: Randomized controlled trials (RCTs) focusing on HIIT program in patients after PCI were searched in Cochrane Library, Web… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Fu C et al (11) believed that rehabilitation exercise after PCI could reduce the risk of coronary artery restenosis and avoid lumen loss at the later stage of the stent coronary artery segment. A Chinese scholar found that personalized exercise training in cardiac rehabilitation could improve cardiac function and exercise endurance, which is an important means of secondary prevention after PCI (12). Therefore, in the perioperative period of PCI for coronary heart disease patients, individualized exercise rehabilitation nursing can be used to reduce the risk of postoperative readmission and promote the improvement of cardiac function indexes.…”
Section: Discussionmentioning
confidence: 99%
“…Fu C et al (11) believed that rehabilitation exercise after PCI could reduce the risk of coronary artery restenosis and avoid lumen loss at the later stage of the stent coronary artery segment. A Chinese scholar found that personalized exercise training in cardiac rehabilitation could improve cardiac function and exercise endurance, which is an important means of secondary prevention after PCI (12). Therefore, in the perioperative period of PCI for coronary heart disease patients, individualized exercise rehabilitation nursing can be used to reduce the risk of postoperative readmission and promote the improvement of cardiac function indexes.…”
Section: Discussionmentioning
confidence: 99%